Do Loyalty Programs Actually Build Customer Loyalty? A Service Quality Perspective from Indonesian e-Commerce - Kosimwidjaja, Jonathan Farrel; Hadiprawoto, Triana (The South East Asian Journal of Management, 2025)
Research Aims: This study investigates the relationship between electronic service quality (e-SERVQUAL), satisfaction and trust, and three indicators of customer loyalty within the context of loyalty programs organised by e-commerce platforms. Design/Methodology/Approach: An empirical approach using purposive sampling was used to generate a population of 326 Indonesian respondents over 18 years old who have used e-commerce loyalty program features such as store credit, points, discount vouchers, cashback vouchers, and free shipping vouchers. Research Findings: Bootstrapped structural equation modelling (SEM) analysis proved that one out of four factors of e-SERVQUAL that apply to e-commerce platforms as a whole do not apply to e-commerce loyalty programs, but the relationships between e-SERVQUAL, satisfaction, trust, and loyalty still stand. Theoretical Contribution/Originality: Measuring e-commerce platform service quality via a specific feature of the platform instead of the platform as a whole shows that perceived quality for e-commerce platform features does not necessarily have the same antecedents as perceived quality for the whole platform. Managerial Implication in the South East Asian Context: When designing loyalty programs for the Indonesian market, Southeast Asian e-commerce platforms should be aware that security, safety and delivering what is promised are more important than the design of the programs (e.g., the visual layout, ease of use, and convenience). Research Limitation & Implications: Customer behavioural data tended to be homogenous for indicators like age and spending amount, not representative of the entire e-commerce landscape in Indonesia; researchers might try quota sampling to alleviate the bias. Alternatively, a longitudinal study can be done to see how different promotions and shopping seasons affect perceived quality.